Improvements of IBS 3D printig mix design material performance with kenaf fiber in the building construction / Muhammad Amirul Haqim Saharan and Muhammad Naim Mahyuddin - Saharan, Muhammad Amirul Haqim; Mahyuddin, Muhammad Naim (2023)
The construction industry has experienced a paradigm shift, leading to a growing demand for sustainable construction methods. 3D printing technology has revolutionized the construction industry by allowing for mass-customization of structures, reducing the need for formwork and labor. However, 3D printing has faced challenges due to unstable and low-strength materials, making it an expensive method. This research aims to find a sustainable material for 3D printing technology in the construction industry, ensuring its strength, cost, and handling methods are superior to those of existing materials. The use of natural building materials from plant waste is crucial for reducing the cost of construction using 3D printing technology in each country. This research aims to find a sustainable material that can be used in 3D printing technology that is used in the construction industry, and make sure that its strength, cost, and handling methods are greater to those of the materials that are already used in building construction. In addition to acquiring more precise data, the goal of this research is to investigate the efficacy of the proposed material (kenaf fibre) for use in Machine 3D Printing and to compare the strength of this new study material with those of materials that have been employed in previous studies. This study shall demonstrates that the Kenaf Fiber Mortar has a compressive strength that meets the requirements of the JKR Mortar Grade 20 Standard Specifications.